Cotard’s syndrome in a patient with major depressive disorder: case report - Huarcaya-Victoria, Jeff (2017)
Cotard’s syndrome is a rare psychiatric condition, first described in 1880 by Jules Cotard, whose central symptom is delusions of negation and which, in its entire form, the patient deny the existence of parts of their bodies or even their whole bodies, leading to denial of the world around them. Ramirez-Bermudez et al. reported that of 479 Mexican patients with a primary psychiatric disorder, including 150 patients with schizophrenia, three had Cotard’s syndrome (0.62%), all of them with psychotic depression. In 2013, Stompe and Schanda reviewed 346 cases of schizophrenia and found three patients with Cotard’s syndrome (0.87%).